Asymmetric Gold-Catalyzed Alkyne Transformations for Synthesis of Axial, Helical, and Planar Chirality - Liu, Guan-Zhi; Nie, Xin; Li, Long (Synthesis, 2025)
Gold-catalyzed asymmetric alkyne transformations have emerged as a powerful strategy for constructing chiral architectures owing to gold’s unique carbophilic π-acidity. This review comprehensively summarizes recent breakthroughs in constructing noncentral chirality, focusing on axial, helical, and planar chiral scaffolds. Beyond that, innovative ligand design and the underlying structure–activity relationships that govern stereocontrol are highlighted in this review. This overview provides insights into current trends in gold-catalyzed asymmetric synthesis.
Keywords: Gold catalysis; Alkynes; Axial chirality; Helical chirality; Planar chirality